Seroepidemiological surveillance, community perceptions and associated risk factors of malaria exposure among forest-goers in Northeastern Thailand - Rahim, Mohd Amirul Fitri A.; Chuangchaiya, Sriwipa; Chanpum, Paisit; Palawong, Laun; Kantee, Panuwat; Dian, Nor Diyana; Lubis, Inke Nadia D.; Divis, Paul C. S.; Kaneko, Akira; Tetteh, Kevin K. A.; Idris, Zulkarnain Md (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria remains a major public health challenge in Thailand. Continuous assessment and understanding of the perceptions related to malaria exposure in the high-risk group are necessary to achieve the elimination goal. This study aimed to investigate the parasite prevalence, seroprevalence rate, knowledge, attitudes and practices (KAP), and malaria risk factors in forest-goer communities in the northeastern part of Thailand. A community-based cross-sectional survey was conducted in three communities (i.e. Ban Khok, Ban Koh, and Dong Yang) located in Khamcha-i district, Mukdahan Province, Thailand, from July to August 2019. Demographic, socio-economic information and KAP data were collected using a structured questionnaire. Parasite prevalence was determined by microscopy. Seroprevalence was determined via ELISA using two Plasmodium falciparum (PfAMA-1 and PfMSP-119) and two Plasmodium vivax (PvAMA-1 and PvMSP-119) antigens. Age-adjusted antibody responses were analysed using a reversible catalytic model to calculate seroconversion rate (SCR). Malaria parasite was not detected in any of the 345 participants. The overall malaria seroprevalence was 72.2% for PfAMA-1, 18.8% for PfMSP-119, 32.5% for PvAMA-1, and 4.4% for PvMSP-119. The proportion of seroprevalence for P. falciparum and P. vivax antigens were significantly highest in Ban Koh (35.1%, P < 0.001) and Don Yang (18.8%, P<0.001), respectively. For all parasite antigens except PvMSP-119, the proportion of seropositive individuals significantly increased with age (P < 0.001). Based on the SCRs, there was a higher level of P. falciparum transmission than P. vivax. Regarding KAP, almost all respondents showed adequate knowledge and awareness about malaria. Nevertheless, significant effort is needed to improve positive attitudes and practices concerning malaria prevention measures. Multivariate regression analyses showed that living in Ban Koh was associated with both P. falciparum (adjusted odds ratio [aOR] 12.87, P < 0.001) and P. vivax (aOR 9.78, P < 0.001) seropositivities. We also found significant associations between age and seropositivity against P. falciparum and P. vivax antigens. The data suggest that seroepidemiological surveillance using AMA-1 and MSP-119 antigens may provide further evidence to reconstruct malaria exposure history. The absent to weak evidence of recent malaria transmission in Mukdahan Province is promising in the context of the disease elimination program.